Crafting theories about living heritage: the postcolonial condition of contemporary Asian architecture and urbanism as an Asian ‘display’ - Lin, Francis Chia Hui (Journal of Asian architecture and building engineering, 2025)
Heritage usually represents how the past is valued today. This paper, however, introduces a new perspective based on historical materialism, which is evident in modern Asian architecture. It argues that contemporary Asian architecture moves away from traditional historicism and embraces different ways of relating to history. The paper explores the idea of “living heritage”, which is shaped by the postcolonial nature of current Asian architecture and urban planning. The core idea is that immediate historicity, the presence of appreciated historical values, creates a unique quality called “display-ness”. This concept involves not just physical, visual, and spatial aspects, but also how a place is institutionalised. As evidence, modern heritage is influenced by global political dynamics. In Asia, the quality of architecture has shifted from modernism to what might be called colonial modernity, showing a new focus on hybridity. By comparing Japan and Singapore, this paper illustrates this idea of display-ness, which suggests a blend of future urban developments and cultural history in the present.